CORPORATE SOCIAL RESPONSIBILITY OF ISLAMIC BANK'S PRACTICES: AN EXPLORATORY STUDY - Jusoh, Wan Noor Hazlina Wan; Ibrahim, Uzaimah (IJIBE (International Journal of Islamic Business Ethics), 2016)
The purpose of this paper is to explore the corporate social responsibility (CSR) practices of an Islamic bank, which is Bank Islam Malaysia Berhad (BIMB). This research used face-to-face interview technique as a research method in order to get data that are more accurate. The data analysis focuses on four CSR themes namely, zakat, charitable activities, employee and environment. The findings show that BIMB has applied CSR practices in various ways and does not merely focussing on zakat and charitable activities as debated in previous studies in other Islamic banks. This paper contributes to the growing debate on CSR among Islamic financial institutions especially in Islamic banking industry by exploring new visibilities.